Factors affecting profit quality in manufacturing companies listed on Indonesia Stock Exchange 2012-1016 - Tutut Murniati (The Indonesian Accounting Review, 2019)
The manufacturing company's profit information is useful for the right decision-making. This study aims to determine the effect of leverage, liquidity, audit firm reputation, conservatism, investment opportunity set (IOS), independent commissioner and institutional ownership of earnings quality at manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2012-2016. This research also use control variable that is return on asset (ROA). The sampling method used is purposive sampling technique. The sample used is as many as 100 manufacturing companies listed on the IDX. Data analysis in this research use multiple linear regression analysis. The results of this study indicate that leverage, liquidity, conservatism, independent commissioner and institutional ownership have no effect on earnings quality either using control variable or without control variable. Investment opportunity set variables affect the quality of earnings when testing without using control variables. While when tested by using control variables, investment opportunity set has no effect on earnings quality. Audit firm reputation has an effect on the quality of earnings both when using control variables and without control variables.